Investigating the effects of language learning strategies teaching on the learning process of efl students with language learning difficulties - Reis, Leonice Passarella dos (2004)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão. Programa de Pós-Graduação em Letras/Inglês e Literatura Correspondente.